THE «POLICY-BLIND» AND «POLICY-COGNIZANT» THEORIES AND MODELS OF RATIONAL CHOICE AS FACTORS OF MINORITY GOVERNMENTS’ EXPLANATION IN PARLIAMENTARY DEMOCRACIES - Панчак-Бялоблоцька, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is dedicated to analysing the «policy-blind» and «policy-cognizant» theories and models of rational choice as factors of minority governments’ explanation in parliamentary democracies. The researcher singled out theoretical and methodological perspectives of research and explanation of minority governments and argued that «policy-blind» theories and models of governments are post-oriented one, so they don’t contribute to minority governments, but instead «policy-cognizant» theories and models of governments are policy-oriented one and therefore significantly contribute to minority governments.